PERLINDUNGAN HUKUM PERJANJIAN PENEMPATAN ANTARA PEKERJA MIGRAN INDONESIA (PMI) DENGAN PERUSAHAAN PENEMPATAN PEKERJA MIGRAN INDONESIA (P3MI) DALAM PERSPEKTIF KITAB UNDANG–UNDANG HUKUM PERDATA DAN UNDANG - UNDANG NOMOR 18 TAHUN 2017 TENTANG PERLINDUNGAN PMI: (Studi Kasus Di PT. Pamor Sapta Dharma Dan PT. Panca Ashma Tunggal) - Topan Hadi Sucipto; Pasaribu, Agnes; Kurniawan Soetijono, Irwan (JURNAL AMAR, 2023)
Legal Protection Of Placement Agreements Between Indonesian Migrant Workers (PMI) And Companies Placement Of Indonesian Migrant Workers (P3MI) In The Perspective Of The Book Of Civil Law And Law Number 18year 2017 On Pmi Protection (Case Study at PT. Pamor Sapta Dharma And PT. Panca Ashma Tunggal) In the work placement agreement between PMI candidates and P3MI, PMI candidates are required to obtain a copy of the agreement document so that later they can fulfill the rights and obligations contained in the work placement agreement, but in reality the PMI candidate is not given a copy of the agreement document by P3MI. The problem in this research is how to implement the placement agreement between PMI and P3MI at PT. Pamor Sapta Dharma and PT. Panca Ashma Tunggal in Banyuwangi. In this thesis, the problem is how the legal protection of the placement agreement for PMI according to Law Number 18 of 2017 and the Civil Code and how the government is trying to provide legal protection for prospective PMI. This type of research is empirical legal research, is a legal research method that uses empirical facts taken from direct sources for PMI and P3MI candidates and related agencies regarding PMI placement, through direct observations on location, interviews and questionnaires. The conclusion of this study is that the implementation of the PMI candidate placement agreement with P3MI PT. Pamor Sapta Dharma and PT. Panca Ashma Tunggal in the Perspective of the Civil Code, by not submitting a copy of the agreement document, PMI candidates do not understand what rights and obligations must be fulfilled to fulfill achievements and P3MI will be more dominant in prosecuting achievements to PMI candidates. The Banyuwangi Regency Government's efforts to provide legal protection for placement agreements between PMI candidates and P3MI are reviewed from Law NO. 18 of 2017 concerning PMI Protection is still lacking, the state must be present in every problem that occurs and provide the best solution for PMI candidates.